Increased energy demand from anabolic-catabolic processes drives β-lactam antibiotic lethality. Issue 2 (17th February 2022) - Lobritz, Michael A.; Andrews, Ian W.; Braff, Dana; Porter, Caroline B.M.; Gutierrez, Arnaud; Furuta, Yoshikazu; Cortes, Louis B.G.; Ferrante, Thomas; Bening, Sarah C.; Wong, Felix; Gruber, Charley; Bakerlee, Christopher W.; et al.
Summary: β-Lactam antibiotics disrupt the assembly of peptidoglycan (PG) within the bacterial cell wall by inhibiting the enzymatic activity of penicillin-binding proteins (PBPs). It was recently shown that β-lactam treatment initializes a futile cycle of PG synthesis and degradation, highlighting major gaps in our understanding of the lethal effects of PBP inhibition by β-lactam antibiotics. Here, we assess the downstream metabolic consequences of treatment of Escherichia coli with the β-lactam mecillinam and show that lethality from PBP2 inhibition is a specific consequence of toxic metabolic shifts induced by energy demand from multiple catabolic and anabolic processes, including accelerated protein synthesis downstream of PG futile cycling. Resource allocation into these processes is coincident with alterations in ATP synthesis and utilization, as well as a broadly dysregulated cellular redox environment. These results indicate that the disruption of normal anabolic-catabolic homeostasis by PBP inhibition is an essential factor for β-lactam antibiotic lethality. Graphical abstract: Highlights: PBP2 inhibition by mecillinam alters bacterial catabolic and anabolic processes Bacterial protein synthesis is identified as a source of energy demand Reactive metabolic by-products are important for mecillinam lethality Target-proximal and downstream metabolic effects contribute to mecillinam lethality Abstract : Lobritz et al. assess the target-proximal and downstream metabolic consequences of treatment of E . coli with the β-lactam mecillinam. They show that lethality from PBP2 inhibition is a specific consequence of toxic metabolic shifts induced by energy demand from multiple catabolic and anabolic processes.